A cemented carbide drill bit and preparation method thereof

By using specific metal powders and nano-alumina and boron oxide agents in cemented carbide drill bits, the problem of difficult to coordinate the wear resistance and fracture toughness of the drill bits is solved, and its high temperature-corrosion stability and bending resistance are improved , improves usage efficiency.

CN118951021BActive Publication Date: 2025-01-14XIANGTAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411449219.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-14
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

The wear resistance, hardness and fracture toughness of existing cemented carbide drill bits are difficult to balance, and the high-temperature-corrosion stability and bending stability are insufficient, which limits the efficiency of the product.

Method used

The drill bit is prepared by mold press molding and segmented sintering processes using metal powders including tungsten carbide powder, cobalt powder, nickel powder, chromium carbide powder and nanobis oxide phase agent. Cooperate to optimize the structure and performance of the drill bit.

Benefits of technology

It significantly improves the hardness, wear resistance and fracture toughness of the drill bit, and at the same time improves the high-temperature-corrosion stability and bending stability, coordinates the hardness and wear resistance, and enhances the overall performance stability of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention relates to the technical field of alloy drill bits, and in particular to a cemented carbide drill bit and a preparation method thereof. The cemented carbide drill bit comprises a drill bit body and a drill rod. The front end of the drill bit body is in a cone shape, and a spiral groove is provided on the side of the cone. The cone structure of the drill bit body is made by pressing and sintering metal powder in a mold. The drill metal powder of the present invention uses tungsten carbide powder, cobalt powder, nickel powder and chromium carbide powder as a matrix material, and is added with a balancing agent and a phase agent doped with nano-bismuth oxide. The metal powder obtained by the coordination and cooperation of the two is then sintered in stages, and the system density is optimized through multi-stage sintering improvement, and the hardness, wear resistance and fracture toughness of the product are coordinated and improved. At the same time, the product has significant effects on high heat-corrosion stability and bending stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of alloy drill bits, and in particular to a cemented carbide drill bit and a preparation method thereof. Background Art

[0002] A drill bit is a tool used to drill through holes or blind holes in solid materials, and can also expand existing holes. Commonly used drill bits include twist drills, flat drills, center drills, deep hole drills and casing drills. Although reaming drills and countersink drills cannot drill holes in solid materials, they are customarily classified as drill bits. When drilling, the drill bit mainly cuts the workpiece through the top of the cutter head and discharges the chips through the chip groove. If the chips cannot be discharged smoothly, scratches will appear on the inner wall of the drilled hole, and even the workpiece will become scrapped.

[0003] The existing cemented carbide drill bits have poor wear resistance, and the wear resistance, hardness and fracture toughness of the product are difficult to coordinate and balance. At the same time, the product has poor high thermal corrosion stability and bending stability, which limits the use efficiency of the product. Based on this, the present invention further improves it. Summary of the invention

[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a cemented carbide drill and a preparation method thereof to solve the problems raised in the above background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution:

[0006] The present invention provides a cemented carbide drill bit, which comprises a drill bit body and a drill rod. The front end of the drill bit body is in a cone shape, and a spiral groove is provided on the side of the cone. The cone structure of the drill bit body is made by pressing and sintering metal powder in a mold.

[0007] The metal powder includes the following raw materials in parts by weight:

[0008] 45-50 parts of tungsten carbide powder, 15-20 parts of cobalt powder, 8-12 parts of nickel powder, 8-11 parts of balancing agent, 7-10 parts of chromium carbide powder, and 4-6 parts of phase agent doped with nano-bismuth oxide.

[0009] Preferably, the pressing pressure is 100-150 MPa, and the pressing time is 20-30 min;

[0010] The specific operation steps of the sintering improvement are:

[0011] First, perform a heat sintering at 450~550℃ for 20~30min, then heat up to 1150℃ at a rate of 5~8℃ / min, perform a second heat sintering for 10~15min, and finally heat up to 1350~1370℃ at a rate of 2~4℃ / min. Perform a third heat sintering for 1~2h. After sintering, air cool to room temperature.

[0012] Preferably, the preparation method of the balancing agent is:

[0013] S01: irradiate the nano-alumina in a proton irradiation box for 5-10 minutes at an irradiation power of 350-400W, and obtain irradiated nano-alumina after the irradiation is completed;

[0014] S02: mixing the irradiated nano-alumina and 2-5% by mass lanthanum chloride solution in a weight ratio of 2:5 to obtain a nano-alumina liquid;

[0015] 2-5 parts of nano-alumina liquid and 1-2 parts of stearic acid are added to 5-8 parts of 5% chitosan solution by mass, and stirred at a speed of 350-450 r / min for 5-10 minutes. After stirring, a nano-alumina solution is obtained;

[0016] S03: Add 5 to 8 parts of boron oxide agent to 12 to 15 parts of 2 to 4% dopamine hydrochloride solution by mass, and then add 2 to 4 parts of barium nitrate aqueous solution, stir well, and obtain a boron oxide equilibrium solution;

[0017] S04: Mix the boron oxide balance solution and the nano-alumina adjustment solution in a weight ratio of 2:5, and after stirring, wash with water and dry to obtain a balance adjustment agent.

[0018] Preferably, the mass fraction of the barium nitrate aqueous solution is 5-8%.

[0019] Preferably, the stirring temperature of the mixed stirring treatment in S04 is 52-55° C., the stirring speed is 400-500 r / min, and the stirring time is 25-30 min.

[0020] Preferably, the preparation method of the boron oxide agent is:

[0021] The boron oxide is heat treated at 120-130°C for 2-5 minutes, and then cooled to 60-65°C at a rate of 2-5°C / min; then ultrasonically immersed in a sufficient amount of an immersion agent, and after the ultrasonication is terminated, the immersion agent is washed with water, filtered, and dried to obtain a boron oxide agent, wherein the immersion agent is a mixture of a 5% by mass sodium silicate solution and a 3% by mass lanthanum nitrate solution in a weight ratio of 2:5.

[0022] Preferably, the ultrasonic power of the ultrasonic immersion treatment is 350-400 W, and the ultrasonic time is 20-30 min.

[0023] Preferably, the preparation method of the phase agent doped with nano-bismuth oxide is:

[0024] S11: mixing nano bismuth oxide, silane coupling agent KH560 and 5% by mass sodium dodecyl sulfate solution in a weight ratio of (2-5):1:(5-8) to obtain nano bismuth oxide solution;

[0025] S12: mixing the carbon fiber in a sufficient amount of a potassium permanganate solution having a mass fraction of 4-6%, and then washing, filtering, and drying to obtain a carbon fiber agent;

[0026] 3-5 parts of carbon fiber agent, 4-7 parts of Tris-HCl buffer solution and 1-3 parts of sodium alginate solution are mixed to obtain a carbon fiber modifier;

[0027] S13: The nano-bismuth oxide liquid and the carbon fiber modifier are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1000-1500 r / min for 1 h. After the ball-milling is completed, the mixture is washed with water, filtered, and dried to obtain a phase agent doped with nano-bismuth oxide.

[0028] Preferably, the pH value of the Tris-HCl buffer solution is 8-9; and the mass fraction of the sodium alginate solution is 5-8%.

[0029] The present invention also provides a method for preparing a cemented carbide drill bit, comprising the following steps:

[0030] Tungsten carbide powder, cobalt powder, nickel powder, balancing agent, chromium carbide powder and a phase agent doped with nano-bismuth oxide are fully mixed to obtain metal powder, the metal powder is pressed into shape in a mold, and then sintered to obtain a drill body. A cone structure is opened at the front end of the drill body, a spiral groove is opened on the side of the cone, and then the drill body and the drill rod are integrated to form a cemented carbide drill bit.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] 1. The cone structure of the drill body of the present invention is improved by pressing and sintering metal powder in a mold. The metal powder is made of tungsten carbide powder, cobalt powder, nickel powder and chromium carbide powder as the base material, and a balancing agent and a phase agent doped with nano-bismuth oxide are added. The metal powder is synergistically obtained by the coordination of the two, and then sintered in stages. The system density is optimized through multi-stage sintering improvement, and the hardness, wear resistance and fracture toughness of the product are coordinated and improved. At the same time, the product has remarkable high heat-corrosion stability and bending stability.

[0033] 2. The balancing agent uses nano-alumina irradiated with protons to optimize its activity efficiency, and then it is coordinated with lanthanum chloride solution to obtain nano-alumina liquid. At the same time, nano-alumina liquid, stearic acid and chitosan solution are blended to obtain nano-alumina adjustment liquid. At the same time, boron oxide agent, dopamine hydrochloride solution and barium nitrate aqueous solution are blended and adjusted to obtain boron oxide balance liquid. Through the coordination and mutual assistance between the raw materials, mutual reinforcement and coordination, the balancing agent obtained can optimize the performance of the product system, coordinate and improve the performance effect and performance stability of the product;

[0034] 3. The boron oxide agent is heat treated at 120-130°C for 2-5 minutes, and then cooled to 60-65°C at a rate of 2-5°C / min to optimize its activity performance. At the same time, sodium silicate solution and 3% by mass lanthanum nitrate solution are blended to obtain an impregnating agent. The impregnating agent is coordinated with the boron oxide raw material to obtain the boron oxide agent to further strengthen and balance the raw materials in the feed agent, so that the performance of the product is further improved;

[0035] 4. The phase agent doped with nano-bismuth oxide is prepared by mixing nano-bismuth oxide, silane coupling agent KH560 and 5% by mass sodium dodecyl sulfate solution to improve the dispersion activity and interfacial effect of nano-bismuth oxide. The carbon fiber is treated with potassium permanganate solution to stimulate its activity efficiency. At the same time, the carbon fiber agent, Tris-HCl buffer solution and sodium alginate solution are fully blended to obtain a carbon fiber modifier. The needle-like structure of the carbon fiber is coordinated with the doped nano-bismuth oxide to obtain the phase agent doped with nano-bismuth oxide as a reinforcing and balancing agent. The coordinated synergistic effect of the two is enhanced, and the performance of the product is further improved. DETAILED DESCRIPTION

[0036] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] A cemented carbide drill bit of this embodiment includes a drill body and a drill rod. The front end of the drill body is in a cone shape, and a spiral groove is provided on the side of the cone. The cone structure of the drill body is made by pressing and sintering metal powder in a mold.

[0038] The metal powder includes the following raw materials by weight:

[0039] 45-50 parts of tungsten carbide powder, 15-20 parts of cobalt powder, 8-12 parts of nickel powder, 8-11 parts of balancing agent, 7-10 parts of chromium carbide powder, and 4-6 parts of phase agent doped with nano-bismuth oxide.

[0040] The pressing pressure of this embodiment is 100~150Mpa, and the pressing time is 20~30min;

[0041] The specific operation steps of the sintering improvement are:

[0042] First, perform a heat sintering at 450~550℃ for 20~30min, then heat up to 1150℃ at a rate of 5~8℃ / min, perform a second heat sintering for 10~15min, and finally heat up to 1350~1370℃ at a rate of 2~4℃ / min. Perform a third heat sintering for 1~2h. After sintering, air cool to room temperature.

[0043] The preparation method of the balancing agent of this embodiment is:

[0044] S01: irradiate the nano-alumina in a proton irradiation box for 5-10 minutes at an irradiation power of 350-400W, and obtain irradiated nano-alumina after the irradiation is completed;

[0045] S02: mixing the irradiated nano-alumina and 2-5% by mass lanthanum chloride solution in a weight ratio of 2:5 to obtain a nano-alumina liquid;

[0046] 2-5 parts of nano-alumina liquid and 1-2 parts of stearic acid are added to 5-8 parts of 5% chitosan solution by mass, and stirred at a speed of 350-450 r / min for 5-10 minutes. After stirring, a nano-alumina solution is obtained;

[0047] S03: Add 5 to 8 parts of boron oxide agent to 12 to 15 parts of 2 to 4% dopamine hydrochloride solution by mass, and then add 2 to 4 parts of barium nitrate aqueous solution, stir well, and obtain a boron oxide equilibrium solution;

[0048] S04: Mix the boron oxide balance solution and the nano-alumina adjustment solution in a weight ratio of 2:5, and after stirring, wash with water and dry to obtain a balance adjustment agent.

[0049] The mass fraction of the barium nitrate aqueous solution in this embodiment is 5-8%.

[0050] The stirring temperature of the mixed stirring treatment in S04 of this embodiment is 52-55° C., the stirring speed is 400-500 r / min, and the stirring time is 25-30 min.

[0051] The preparation method of the boron oxide agent of this embodiment is:

[0052] The boron oxide is heat treated at 120-130°C for 2-5 minutes, and then cooled to 60-65°C at a rate of 2-5°C / min; then ultrasonically immersed in a sufficient amount of an immersion agent, and after the ultrasonication is terminated, the immersion agent is washed with water, filtered, and dried to obtain a boron oxide agent, wherein the immersion agent is a mixture of a 5% by mass sodium silicate solution and a 3% by mass lanthanum nitrate solution in a weight ratio of 2:5.

[0053] The ultrasonic power of the ultrasonic immersion treatment in this embodiment is 350-400 W, and the ultrasonic time is 20-30 min.

[0054] The preparation method of the phase agent doped with nano-bismuth oxide in this embodiment is as follows:

[0055] S11: mixing nano bismuth oxide, silane coupling agent KH560 and 5% by mass sodium dodecyl sulfate solution in a weight ratio of (2-5):1:(5-8) to obtain nano bismuth oxide solution;

[0056] S12: mixing the carbon fiber in a sufficient amount of a potassium permanganate solution having a mass fraction of 4-6%, and then washing, filtering, and drying to obtain a carbon fiber agent;

[0057] 3-5 parts of carbon fiber agent, 4-7 parts of Tris-HCl buffer solution and 1-3 parts of sodium alginate solution are mixed to obtain a carbon fiber modifier;

[0058] S13: The nano-bismuth oxide liquid and the carbon fiber modifier are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1000-1500 r / min for 1 h. After the ball-milling is completed, the mixture is washed with water, filtered, and dried to obtain a phase agent doped with nano-bismuth oxide.

[0059] The pH value of the Tris-HCl buffer solution of this embodiment is 8-9; the mass fraction of the sodium alginate solution is 5-8%. A method for preparing a cemented carbide drill bit of this embodiment comprises the following steps:

[0060] Tungsten carbide powder, cobalt powder, nickel powder, balancing agent, chromium carbide powder and a phase agent doped with nano-bismuth oxide are fully mixed to obtain metal powder, the metal powder is pressed into shape in a mold, and then sintered to obtain a drill body. A cone structure is opened at the front end of the drill body, a spiral groove is opened on the side of the cone, and then the drill body and the drill rod are integrated to form a cemented carbide drill bit.

[0061] Example 1

[0062] A cemented carbide drill bit of this embodiment includes a drill body and a drill rod. The front end of the drill body is in a cone shape, and a spiral groove is provided on the side of the cone. The cone structure of the drill body is made by pressing and sintering metal powder in a mold.

[0063] The metal powder includes the following raw materials by weight:

[0064] 45 parts of tungsten carbide powder, 15 parts of cobalt powder, 8 parts of nickel powder, 8 parts of balancing agent, 7 parts of chromium carbide powder, and 4 parts of phase agent doped with nano-bismuth oxide.

[0065] The pressing pressure of this embodiment is 100Mpa and the pressing time is 20min;

[0066] The specific operation steps of the sintering improvement are:

[0067] First, perform a heat sintering at 450°C for 20 minutes, then heat up to 1150°C at a rate of 5°C / min, perform a second heat sintering for 10 minutes, and finally heat up to 1350°C at a rate of 2°C / min. Perform a third heat sintering for 2 hours. After sintering, cool to room temperature in air.

[0068] The preparation method of the balancing agent of this embodiment is:

[0069] S01: irradiate the nano-alumina in a proton irradiation box for 5 minutes at an irradiation power of 350W, and obtain irradiated nano-alumina after the irradiation is completed;

[0070] S02: mixing the irradiated nano-alumina and 2% by mass lanthanum chloride solution in a weight ratio of 2:5 to obtain a nano-alumina liquid;

[0071] 2 parts of nano-alumina liquid and 1 part of stearic acid were added to 5 parts of 5% chitosan solution by mass, and stirred at a speed of 350 r / min for 5 minutes. After the stirring was completed, the nano-alumina solution was obtained.

[0072] S03: Add 5 parts of boron oxide to 12 parts of 2% dopamine hydrochloride solution, then add 2 parts of barium nitrate aqueous solution, stir thoroughly, and obtain a boron oxide equilibrium solution;

[0073] S04: Mix the boron oxide balance solution and the nano-alumina adjustment solution in a weight ratio of 2:5, and after stirring, wash with water and dry to obtain a balance adjustment agent.

[0074] The mass fraction of the barium nitrate aqueous solution in this embodiment is 5%.

[0075] The stirring temperature of the mixed stirring treatment in S04 of this embodiment is 52° C., the stirring speed is 400 r / min, and the stirring time is 25 min.

[0076] The preparation method of the boron oxide agent of this embodiment is:

[0077] The boron oxide is heat treated at 120°C for 2 minutes, and then cooled to 60°C at a rate of 2°C / min; then ultrasonically immersed in a sufficient amount of an impregnating agent, and after the ultrasonication is terminated, the boron oxide agent is washed with water, filtered, and dried to obtain a boron oxide agent, wherein the impregnating agent is a mixture of a 5% by mass sodium silicate solution and a 3% by mass lanthanum nitrate solution in a weight ratio of 2:5.

[0078] The ultrasonic power of the ultrasonic immersion treatment in this embodiment is 3500W, and the ultrasonic time is 20 minutes.

[0079] The preparation method of the phase agent doped with nano-bismuth oxide in this embodiment is as follows:

[0080] S11: mixing nano bismuth oxide, silane coupling agent KH560 and 5% by mass sodium dodecyl sulfate solution in a weight ratio of 2:1:5 to obtain nano bismuth oxide solution;

[0081] S12: mixing the carbon fiber in a sufficient amount of a 4% by mass potassium permanganate solution, and then washing, filtering, and drying to obtain a carbon fiber agent;

[0082] 3 parts of carbon fiber agent, 4 parts of Tris-HCl buffer solution and 1 part of sodium alginate solution are fully mixed to obtain a carbon fiber modifier;

[0083] S13: The nano-bismuth oxide liquid and the carbon fiber modifier are mixed in a weight ratio of 5:3, and the mixture is ball-milled at a speed of 1000 r / min for 1 h. After the ball-milling is completed, the mixture is washed with water, filtered, and dried to obtain a phase agent doped with nano-bismuth oxide.

[0084] The pH value of the Tris-HCl buffer solution in this embodiment is 8; the mass fraction of the sodium alginate solution is 5%.

[0085] A method for preparing a cemented carbide drill bit in this embodiment comprises the following steps:

[0086] Tungsten carbide powder, cobalt powder, nickel powder, balancing agent, chromium carbide powder and a phase agent doped with nano-bismuth oxide are fully mixed to obtain metal powder, the metal powder is pressed into shape in a mold, and then sintered to obtain a drill body. A cone structure is opened at the front end of the drill body, a spiral groove is opened on the side of the cone, and then the drill body and the drill rod are integrated to form a cemented carbide drill bit.

[0087] Example 2

[0088] A cemented carbide drill bit of this embodiment includes a drill body and a drill rod. The front end of the drill body is in a cone shape, and a spiral groove is provided on the side of the cone. The cone structure of the drill body is made by pressing and sintering metal powder in a mold.

[0089] The metal powder includes the following raw materials by weight:

[0090] 50 parts of tungsten carbide powder, 20 parts of cobalt powder, 12 parts of nickel powder, 11 parts of balancing agent, 10 parts of chromium carbide powder, and 6 parts of phase agent doped with nano-bismuth oxide.

[0091] The pressing pressure of this embodiment is 150Mpa and the pressing time is 30min;

[0092] The specific operation steps of the sintering improvement are:

[0093] First, perform a heat sintering at 550°C for 30 minutes, then heat up to 1150°C at a rate of 8°C / min, perform a second heat sintering for 15 minutes, and finally heat up to 1370°C at a rate of 4°C / min. Perform a third heat sintering for 2 hours. After sintering, cool to room temperature in air.

[0094] The preparation method of the balancing agent of this embodiment is:

[0095] S01: irradiating the nano-alumina in a proton irradiation box for 10 minutes at an irradiation power of 400W, and obtaining irradiated nano-alumina after the irradiation is completed;

[0096] S02: mixing the irradiated nano-alumina and 5% by mass lanthanum chloride solution in a weight ratio of 2:5 to obtain a nano-alumina liquid;

[0097] 5 parts of nano-alumina liquid and 2 parts of stearic acid were added to 8 parts of 5% chitosan solution, and stirred at a speed of 450 r / min for 10 minutes. After the stirring was completed, the nano-alumina solution was obtained.

[0098] S03: adding 8 parts of boron oxide agent to 15 parts of 4% dopamine hydrochloride solution, and then adding 4 parts of barium nitrate aqueous solution, stirring thoroughly, to obtain a boron oxide equilibrium solution;

[0099] S04: Mix the boron oxide balance solution and the nano-alumina adjustment solution in a weight ratio of 2:5, and after stirring, wash with water and dry to obtain a balance adjustment agent.

[0100] The mass fraction of the barium nitrate aqueous solution in this embodiment is 8%.

[0101] The stirring temperature of the mixed stirring treatment in S04 of this embodiment is 55° C., the stirring speed is 500 r / min, and the stirring time is 30 min.

[0102] The preparation method of the boron oxide agent of this embodiment is:

[0103] The boron oxide is heat treated at 130°C for 5 minutes, and then cooled to 65°C at a rate of 5°C / min; then ultrasonically immersed in a sufficient amount of an impregnating agent, and after the ultrasonication is terminated, the boron oxide agent is washed with water, filtered, and dried to obtain a boron oxide agent, wherein the impregnating agent is a mixture of a 5% by mass sodium silicate solution and a 3% by mass lanthanum nitrate solution in a weight ratio of 2:5.

[0104] The ultrasonic power of the ultrasonic immersion treatment in this embodiment is 400 W, and the ultrasonic time is 30 min.

[0105] The preparation method of the phase agent doped with nano-bismuth oxide in this embodiment is as follows:

[0106] S11: mixing nano bismuth oxide, silane coupling agent KH560 and 5% by mass sodium dodecyl sulfate solution in a weight ratio of 5:1:8 to obtain nano bismuth oxide solution;

[0107] S12: mixing the carbon fiber in a sufficient amount of a 6% by mass potassium permanganate solution, and then washing, filtering, and drying to obtain a carbon fiber agent;

[0108] 5 parts of carbon fiber agent, 7 parts of Tris-HCl buffer solution and 3 parts of sodium alginate solution are fully blended to obtain a carbon fiber modifier;

[0109] S13: The nano-bismuth oxide liquid and the carbon fiber modifier are mixed in a weight ratio of 5:3, and the mixture is ball-milled at a speed of 1500 r / min for 1 h. After the ball-milling is completed, the mixture is washed with water, filtered, and dried to obtain a phase agent doped with nano-bismuth oxide.

[0110] The pH value of the Tris-HCl buffer solution in this embodiment is 9; the mass fraction of the sodium alginate solution is 8%.

[0111] A method for preparing a cemented carbide drill bit in this embodiment comprises the following steps:

[0112] Tungsten carbide powder, cobalt powder, nickel powder, balancing agent, chromium carbide powder and a phase agent doped with nano-bismuth oxide are fully mixed to obtain metal powder, the metal powder is pressed into shape in a mold, and then sintered to obtain a drill body. A cone structure is opened at the front end of the drill body, a spiral groove is opened on the side of the cone, and then the drill body and the drill rod are integrated to form a cemented carbide drill bit.

[0113] Example 3

[0114] A cemented carbide drill bit of this embodiment includes a drill body and a drill rod. The front end of the drill body is in a cone shape, and a spiral groove is provided on the side of the cone. The cone structure of the drill body is made by pressing and sintering metal powder in a mold.

[0115] The metal powder includes the following raw materials by weight:

[0116] 47.5 parts of tungsten carbide powder, 17.5 parts of cobalt powder, 10 parts of nickel powder, 9.5 parts of balancing agent, 8.5 parts of chromium carbide powder, and 5 parts of phase agent doped with nano-bismuth oxide.

[0117] The pressing pressure of this embodiment is 125Mpa, and the pressing time is 25min;

[0118] The specific operation steps of the sintering improvement are:

[0119] First, heat sintering is performed at 500°C for 25 minutes, then the temperature is increased to 1150°C at a rate of 6.5°C / min, the temperature is increased to 1360°C at a rate of 3°C / min, the temperature is increased to 1360°C for 1.5 hours, and the sintering is completed before air cooling to room temperature.

[0120] The preparation method of the balancing agent of this embodiment is:

[0121] S01: irradiating the nano-alumina in a proton irradiation box for 7.5 minutes with an irradiation power of 370W, and obtaining irradiated nano-alumina after the irradiation is completed;

[0122] S02: mixing the irradiated nano-alumina and 3.5% by mass lanthanum chloride solution in a weight ratio of 2:5 to obtain a nano-alumina liquid;

[0123] 3.5 parts of nano-alumina liquid and 1.5 parts of stearic acid were added to 6.5 parts of 5% chitosan solution, and stirred at a speed of 400 r / min for 7.5 min. After stirring, a nano-alumina solution was obtained.

[0124] S03: Add 6.5 parts of boron oxide to 13.5 parts of 3% dopamine hydrochloride solution, then add 3 parts of barium nitrate aqueous solution, stir well, and obtain a boron oxide equilibrium solution;

[0125] S04: Mix the boron oxide balance solution and the nano-alumina adjustment solution in a weight ratio of 2:5, and after stirring, wash with water and dry to obtain a balance adjustment agent.

[0126] The mass fraction of the barium nitrate aqueous solution in this embodiment is 6.5%.

[0127] The stirring temperature of the mixed stirring process in S04 of this embodiment is 53.5° C., the stirring speed is 450 r / min, and the stirring time is 27.5 min.

[0128] The preparation method of the boron oxide agent of this embodiment is:

[0129] The boron oxide is heat treated at 125°C for 3.5 minutes, and then cooled to 62.5°C at a rate of 3.5°C / min; then ultrasonically immersed in a sufficient amount of an impregnating agent, and after the ultrasonication is terminated, the boron oxide agent is washed with water, filtered, and dried to obtain a boron oxide agent, wherein the impregnating agent is a mixture of a 5% by mass sodium silicate solution and a 3% by mass lanthanum nitrate solution in a weight ratio of 2:5.

[0130] The ultrasonic power of the ultrasonic immersion treatment in this embodiment is 370 W, and the ultrasonic time is 25 min.

[0131] The preparation method of the phase agent doped with nano-bismuth oxide in this embodiment is as follows:

[0132] S11: mixing nano bismuth oxide, silane coupling agent KH560 and 5% by mass sodium dodecyl sulfate solution in a weight ratio of 3.5:1:6.5 to obtain nano bismuth oxide solution;

[0133] S12: mixing the carbon fiber in a sufficient amount of 5% by mass potassium permanganate solution, then washing, filtering, and drying to obtain a carbon fiber agent;

[0134] 4 parts of carbon fiber agent, 5.5 parts of Tris-HCl buffer solution and 2 parts of sodium alginate solution are fully mixed to obtain a carbon fiber modifier;

[0135] S13: The nano-bismuth oxide liquid and the carbon fiber modifier are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1250 r / min for 1 h. After the ball-milling is completed, the mixture is washed with water, filtered, and dried to obtain a phase agent doped with nano-bismuth oxide.

[0136] The pH value of the Tris-HCl buffer solution in this embodiment is 8.5; the mass fraction of the sodium alginate solution is 6.5%.

[0137] A method for preparing a cemented carbide drill bit in this embodiment comprises the following steps:

[0138] Tungsten carbide powder, cobalt powder, nickel powder, balancing agent, chromium carbide powder and a phase agent doped with nano-bismuth oxide are fully mixed to obtain metal powder, the metal powder is pressed into shape in a mold, and then sintered to obtain a drill body. A cone structure is opened at the front end of the drill body, a spiral groove is opened on the side of the cone, and then the drill body and the drill rod are integrated to form a cemented carbide drill bit.

[0139] Comparative Example 1

[0140] The difference from Example 3 is that no balancing agent is added to the metal powder.

[0141] Comparative Example 2

[0142] The difference from Example 3 is that no nano-alumina adjusting liquid is added in the preparation of the balancing adjusting agent.

[0143] Comparative Example 3

[0144] The difference from Example 3 is that no nano alumina liquid is added in the preparation of the nano alumina liquid.

[0145] Comparative Example 4

[0146] The difference from Example 3 is that the nano-alumina liquid is replaced by nano-alumina.

[0147] Comparative Example 5

[0148] The difference from Example 3 is that no boron oxide balance solution is added in the preparation of the balancing agent.

[0149] Comparative Example 6

[0150] The difference from Example 3 is that no barium nitrate aqueous solution is added in the preparation of the boron oxide equilibrium solution, and deionized water is used instead of the dopamine hydrochloride solution.

[0151] Comparative Example 7

[0152] The difference from Example 3 is that no boron oxide agent is added to the boron oxide equilibrium solution.

[0153] Comparative Example 8

[0154] The difference from Example 3 is that no phase agent doped with nano-bismuth oxide is added.

[0155] Comparative Example 9

[0156] The difference from Example 3 is that no carbon fiber modifier is added in the preparation of the phase agent doped with nano-bismuth oxide.

[0157] Comparative Example 10

[0158] The difference from Example 3 is that no carbon fiber agent is added to the carbon fiber modifier.

[0159] Comparative Example 11

[0160] The difference from Example 3 is that no Tris-HCl buffer solution and sodium alginate solution are added to the carbon fiber modifier, and deionized water is used instead.

[0161] Comparative Example 12

[0162] The difference from Example 3 is that no nano-bismuth oxide liquid is added in the preparation of the phase agent doped with nano-bismuth oxide.

[0163] Comparative Example 13

[0164] The difference from Example 3 is that the nano bismuth oxide liquid is replaced by nano bismuth oxide.

[0165] Comparative Example 14

[0166] The difference from Example 3 is that the sintering is improved by using a temperature of 1360° C. for 2 h instead.

[0167] The products of Examples 1 to 3 and Comparative Examples 1 to 14 were subjected to conventional performance tests, and the product results are as follows. Table 1 is a table of product performance test results under conventional conditions;

[0168] Table 1

[0169]

[0170] It can be seen from Comparative Examples 1 to 14 and Examples 1 to 3 that;

[0171] The product of Example 3 has excellent hardness, fracture toughness and wear resistance, and the hardness, fracture toughness and wear resistance can be improved in a coordinated manner. The product performance of Comparative Examples 1-14 is not as good as the product performance effect of Examples 1-3 of the present invention;

[0172] The products of Examples 1-3 and Comparative Examples 1-14 were heat treated at 75°C for 12 hours, and then placed under 2% sodium chloride salt spray conditions for 12 hours. The above was one cycle, and the cycle was repeated 20 times to test the high temperature resistance and corrosion resistance stability of the products. At the same time, the products were treated with a 1000MPa bending strength for 10 times, each treatment for 2 minutes, to test the bending stability of the products. Table 2 is a product performance test table under high temperature resistance, corrosion resistance and bending resistance conditions;

[0173] Table 2

[0174]

[0175] It can be seen from Comparative Examples 1 to 14 and Example 3 that the performance stability of the product deteriorates significantly when no balancing agent or phase agent doped with nano-bismuth oxide is added to the metal powder. The performance effect of the product is most significant when the balancing agent and the phase agent doped with nano-bismuth oxide are coordinated and matched.

[0176] The performance of the products showed a trend of deterioration when no nano-alumina adjusting liquid was added to the preparation of the balancing agent, no nano-alumina liquid was added to the preparation of the nano-alumina adjusting liquid, nano-alumina liquid was replaced by nano-alumina, no boron oxide balancing liquid was added to the preparation of the balancing agent, no barium nitrate aqueous solution was added to the preparation of the boron oxide balancing liquid, deionized water was used to replace the dopamine hydrochloride solution, and no boron oxide agent was added to the boron oxide balancing liquid. The balancing agent obtained by combining the boron oxide balancing liquid obtained by the specific method of the present invention with the specific nano-alumina liquid had the most significant product performance effect. The performance of the product also showed a relatively obvious trend of deterioration when no boron oxide agent was added to the boron oxide balancing liquid.

[0177] Only the balancing agent obtained by the method of the present invention has the most significant product performance effect, and other methods are not as obvious as the effect of the present invention;

[0178] In the preparation of the phase agent doped with nano-bismuth oxide, no carbon fiber modifier was added, no carbon fiber agent was added to the carbon fiber modifier, no Tris-HCl buffer solution and sodium alginate solution were added to the carbon fiber modifier and deionized water was used instead, and in the preparation of the phase agent doped with nano-bismuth oxide, no nano-bismuth oxide liquid was added, and the nano-bismuth oxide liquid was replaced by nano-bismuth oxide. The performance of the products all showed a trend of deterioration to varying degrees. The nano-bismuth oxide liquid and the carbon fiber modifier obtained by the specific method of the present invention adopted the coordinated cooperation between the raw materials and the synergistic effect, and the product performance effect was the most significant. At the same time, the sintering improvement was replaced by sintering at a temperature of 1360° C. for 2 hours, and the performance of the product also showed a trend of deterioration. The sintering improvement effect of the present invention was the best.

[0179] Based on the fact that boron oxide has a significant impact on the performance of the product, further research is conducted on this:

[0180] Experimental Example 1

[0181] The only difference from Example 3 is that the boron oxide agent is not heat treated at 125°C for 3.5 min, but is cooled to 62.5°C at a rate of 3.5°C / min.

[0182] Experimental Example 2

[0183] The only difference from Example 3 is that the boron oxide agent is not treated by ultrasonic immersion of the immersion agent.

[0184] Experimental Example 3

[0185] The only difference from Example 3 is that no sodium silicate solution is added to the impregnating agent.

[0186] Experimental Example 4

[0187] The only difference from Example 3 is that no lanthanum nitrate solution is added to the impregnating agent.

[0188] Taking the test under high temperature resistance, corrosion resistance and bending resistance as an example, the product is further tested for performance. The test results are as follows. Table 3 is a test result table of the effect of boron oxide on the performance of the product;

[0189] Table 3

[0190]

[0191] It can be seen from Experimental Examples 1-4 that the boron oxide agent is not treated with ultrasonic immersion of the immersion agent, and the performance of the product deteriorates significantly. At the same time, no sodium silicate solution is added to the immersion agent, and no lanthanum nitrate solution is added to the immersion agent. The performance of the product has a tendency to deteriorate. The immersion agent obtained by the specific method of the present invention is used for treatment, and the product performance effect is the most significant. At the same time, the preparation conditions of the boron oxide agent are different, and the performance of the product also shows a tendency to deteriorate. The raw materials in the preparation of the boron oxide agent are indispensable, the preparation conditions are changed, and other methods are used instead, which are not as significant as the effects of the present invention.

[0192] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0193] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A cemented carbide drill, comprising a drill body and a drill rod, characterized in that: The front end of the drill body is in a cone shape, and a spiral groove is provided on the side of the cone. The cone structure of the drill body is made by pressing and sintering metal powder in a mold. The metal powder includes the following raw materials in parts by weight: 45-50 parts of tungsten carbide powder, 15-20 parts of cobalt powder, 8-12 parts of nickel powder, 8-11 parts of balancing agent, 7-10 parts of chromium carbide powder, 4-6 parts of phase agent doped with nano-bismuth oxide; The preparation method of the balancing agent is as follows: S01: irradiate the nano-alumina in a proton irradiation box for 5-10 minutes at an irradiation power of 350-400W, and obtain irradiated nano-alumina after the irradiation is completed; S02: mixing the irradiated nano-alumina and 2-5% by mass lanthanum chloride solution in a weight ratio of 2:5 to obtain a nano-alumina liquid; 2-5 parts of nano-alumina liquid and 1-2 parts of stearic acid are added to 5-8 parts of 5% chitosan solution by mass, and stirred at a speed of 350-450 r / min for 5-10 minutes. After stirring, a nano-alumina solution is obtained; S03: Add 5 to 8 parts of boron oxide agent to 12 to 15 parts of 2 to 4% dopamine hydrochloride solution by mass, and then add 2 to 4 parts of barium nitrate aqueous solution, stir well, and obtain a boron oxide equilibrium solution; S04: Mix the boron oxide balance solution and the nano-alumina adjustment solution in a weight ratio of 2:5, and after stirring, wash with water and dry to obtain a balance adjustment agent.

2. A cemented carbide drill according to claim 1, characterized in that: The pressing pressure is 100-150 MPa, and the pressing time is 20-30 min; The specific operation steps of the sintering improvement are: First, perform a heat sintering at 450~550℃ for 20~30min, then heat up to 1150℃ at a rate of 5~8℃ / min, perform a second heat sintering for 10~15min, and finally heat up to 1350~1370℃ at a rate of 2~4℃ / min. Perform a third heat sintering for 1~2h. After sintering, air cool to room temperature.

3. A cemented carbide drill according to claim 1, characterized in that: The mass fraction of the barium nitrate aqueous solution is 5-8%.

4. A cemented carbide drill according to claim 3, characterized in that: The stirring temperature of the mixed stirring treatment in S04 is 52-55° C., the stirring speed is 400-500 r / min, and the stirring time is 25-30 min.

5. A cemented carbide drill according to claim 3, characterized in that: The preparation method of the boron oxide agent is: The boron oxide is heat treated at 120-130°C for 2-5 minutes, and then cooled to 60-65°C at a rate of 2-5°C / min; then ultrasonically immersed in a sufficient amount of an immersion agent, and after the ultrasonication is terminated, the immersion agent is washed with water, filtered, and dried to obtain a boron oxide agent, wherein the immersion agent is a mixture of a 5% by mass sodium silicate solution and a 3% by mass lanthanum nitrate solution in a weight ratio of 2:

5.

6. A cemented carbide drill according to claim 5, characterized in that: The ultrasonic power of the ultrasonic immersion treatment is 350-400W, and the ultrasonic time is 20-30min.

7. A cemented carbide drill according to claim 1, characterized in that: The preparation method of the phase agent doped with nano bismuth oxide is as follows: S11: mixing nano bismuth oxide, silane coupling agent KH560 and 5% by mass sodium dodecyl sulfate solution in a weight ratio of (2-5):1:(5-8) to obtain nano bismuth oxide solution; S12: mixing the carbon fiber in a sufficient amount of a potassium permanganate solution having a mass fraction of 4-6%, and then washing, filtering, and drying to obtain a carbon fiber agent; 3-5 parts of carbon fiber agent, 4-7 parts of Tris-HCl buffer solution and 1-3 parts of sodium alginate solution are mixed to obtain a carbon fiber modifier; S13: The nano-bismuth oxide liquid and the carbon fiber modifier are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1000-1500 r / min for 1 h. After the ball-milling is completed, the mixture is washed with water, filtered, and dried to obtain a phase agent doped with nano-bismuth oxide.

8. A cemented carbide drill according to claim 7, characterized in that: The pH value of the Tris-HCl buffer solution is 8-9; the mass fraction of the sodium alginate solution is 5-8%.

9. The method for preparing a cemented carbide drill according to any one of claims 1 to 8, characterized in that: The following steps are involved: Tungsten carbide powder, cobalt powder, nickel powder, balancing agent, chromium carbide powder and a phase agent doped with nano-bismuth oxide are fully mixed to obtain metal powder, the metal powder is pressed into shape in a mold, and then sintered to obtain a drill body. A cone structure is opened at the front end of the drill body, a spiral groove is opened on the side of the cone, and then the drill body and the drill rod are integrated to form a cemented carbide drill bit.

Citation Information

Patent Citations

  • Deep hole drill

    CN104400080A

  • Wear-resistant high-thermal-conductivity sintered alloy especially suitable for bearings and valve seat rings

    CN114425617A